Value-based utility broker for jitter management of voice on IP networks - Pedrasa, Jhoanna Rhodette I.; Festin, Cedric Angelo M.
A variety of scheduling algorithms and management frameworks have been proposed to provide more than just best effort service offered by the Internet Protocol. A new framework, Value-Based Utility (VBU), uses the perceived knowledge of the state and degree of user satisfaction in managing router resources and functions. VBU has been shown to effectively manage packet loss and delay in times of high demand and low resource availability. This paper applies VBU to jitter management by enhancing on two existing scheduling algorithms, namely Stop and Go and Jitter EDD. Our results show that Stop and Go with Utility can achieve a tigher jitter bound of T, where T is the frame length, which is half of the original bound of 2T offered by Stop and Go alone. VBU has limited application however to Jitter-EDD, where the rigid environment restricts the re-allocation of resources according to demand.
Keywords: Internet telephony; Computer network protocols; TCP/IP (Computer network protocol); Internetworking (Telecommunication)